THE Role of Indonesian National Police in Preventing The Spread of Covid-19 from The Perspective of Fiqh Siyasah - Musyafaah, Nur Lailatul; Rohmah, Maulidatur; Yolanda, Yue Sevin Eva; Izza, Zakiya (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2021)
The article discusses the role of the Indonesian police in preventing the spread of the covid-19 virus from a fiqh siyasah perspective with a statutory approach. Research data were obtained from primary legal materials, namely laws, and regulations related to the Indonesian National Police. Secondary legal materials were collected from books, articles, and news and analyzed descriptively with a deductive mindset. Data on the role of the police during the Covid-19 pandemic based on Law No. 2 of 2002 concerning the National Police of the Republic of Indonesia was analyzed with a review of fiqh siyasah. This research concludes that the Indonesian National Police agency acts as an instrument of law enforcement and supports the success of the Indonesian government in dealing with covid-19. Among the duties of the Indonesian National Police during the Covid-19 pandemic are enforcing the law, educating the public, detecting the spread of the covid-19 virus early, and maintaining security. The police force adheres to the role of al-hisbah in fiqh siyasah, aiming to invite people to act appropriately and prevent people from committing crimes.